2014
DOI: 10.4103/2231-0754.143476
|View full text |Cite
|
Sign up to set email alerts
|

Oral Pathology in Clinical Dentistry: A systematic approach

Abstract: The dental clinician frequently comes across lesions that involve the hard and soft tissues of the oral cavity. Most of these conditions do not pose a diagnostic problem for the dental surgeon. However, the clinical dentist is sometimes accosted with a lesion, the diagnosis of which is not only challenging, but influencing the choice of treatment. This review article provides a systematic and logical approach for diagnosing common lesions encountered in the dental practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Dentists and oral health therapists are often the first point of contact when orofacial pathology is suspected. Having knowledge of oral pathology, dental clinicians can become involved in diagnosing pathology such as the precursor lesions of oral carcinoma (Subramanyam, 2014). Oral health therapists may refer patients to dentists, who may undertake procedures such as a biopsy, or may order diagnostic tests which would be processed by medical laboratory scientists.…”
Section: Innovationmentioning
confidence: 99%
“…Dentists and oral health therapists are often the first point of contact when orofacial pathology is suspected. Having knowledge of oral pathology, dental clinicians can become involved in diagnosing pathology such as the precursor lesions of oral carcinoma (Subramanyam, 2014). Oral health therapists may refer patients to dentists, who may undertake procedures such as a biopsy, or may order diagnostic tests which would be processed by medical laboratory scientists.…”
Section: Innovationmentioning
confidence: 99%
“…3,4 A thorough oral lesion description must include the following nine items: size (length, width, and height), number (single, multiple), outline (regular, irregular), surface (smooth, granular, verrucous, papillomatous, pebbly, cobblestone), base (pedunculated, sessile, nodular, domeshaped), site (mucosal, intra-bony, dental), color (red, pink, white, red-white combined, blue, purple, gray, yellow, black, or brown according to their prevalence in oral mucosa), consistency (soft, hard, cheesy, firm, rubbery, and fluctuant), origin (acquired, non-acquired), and morphology or clinical appearance (primary lesions, secondary lesions). 2,[5][6][7] The morphology component is the most challenging aspect of lesion description, which is the main purpose of this review. Study by Zimmermann and colleagues demonstrated that, when lesions have been described based on a guideline and standard definitions in medicine referrals, information quality was higher compared to cases based on a free.…”
Section: Introductionmentioning
confidence: 99%